1997
DOI: 10.2307/282513
|View full text |Cite
|
Sign up to set email alerts
|

Medieval Climatic Anomaly and Punctuated Cultural Evolution in Coastal Southern California

Abstract: Only in the last few years have high-resolution paleoclimatic data become available from coastal southern California. Recent research in the California Channel Islands, drawing on some of these data, attributes settlement disruptions, disease, and violence to maritime subsistence distress attendant to elevated sea temperatures in the period from A.D. 1150 to 1300. A broad range of paleoenvironmental, archaeological, and human osteological data suggest that these stress indicators are more convincingly correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 38 publications
2
87
0
Order By: Relevance
“…Cool SSTs between $1500 and 500 cal yr BP also correlate with lower precipitation evident in a shorter tree ring record from the coastal ranges of Southern California (Larson and Michaelson, 1989;Kennett and Kennett, 2000). Several other lines of evidence also indicate dry conditions during this interval (Graumlich, 1993;Stine, 1994;Raab and Larson, 1997;.…”
Section: Associated Terrestrial Climate Changesmentioning
confidence: 92%
“…Cool SSTs between $1500 and 500 cal yr BP also correlate with lower precipitation evident in a shorter tree ring record from the coastal ranges of Southern California (Larson and Michaelson, 1989;Kennett and Kennett, 2000). Several other lines of evidence also indicate dry conditions during this interval (Graumlich, 1993;Stine, 1994;Raab and Larson, 1997;.…”
Section: Associated Terrestrial Climate Changesmentioning
confidence: 92%
“…With this proposal, Arnold broke from previous characterizations of human response to environmental problems of the Medieval era by identifying positive developments (e.g., increased bead production and emergent sociopolitical complexity) as opposed to strictly negative ones. While the paleoenvironmental premises underlying her model were ultimately found to be faulty (see Raab and Larson, 1997;Kennett and Kennett, 2000;Kennett, 2005), Arnold identified a strong pattern in the Island archaeological record that runs counter to previous characterizations of exchange trends during the Medieval Period. While the earlier proposals were susceptible to the charge of environmental determinism (positing an inevitable crisislike response to drought), Arnold's model suggested that environmental flux could prompt changes of varied character.…”
Section: Land Versus Sea and The Problem Of Environmental Determinismmentioning
confidence: 99%
“…Using osteological data collected by Lambert and Walker from the Santa Barbara Channel (Walker, 1989;Walker and Lambert, 1989;Lambert and Walker, 1991;Lambert, 1993), Raab and Larson (1997) argued that peaks in cribra orbitalia, periosteal lesions (caused by infectious diseases), and cranial fractures (caused by inter-group conflict) were evident during the MCA as a result of the types of social crises that Moratto et al (1978) proposed earlier. While data supporting this argument were fairly compelling, it must also be recognized that chronological resolution was far from perfect and that peaks in violence and poor health were ascribed to a broad period between ca.…”
Section: Health and Violence: Osteological Signs Of Crisismentioning
confidence: 99%
See 2 more Smart Citations